Inversion of AMSR‐E observations for land surface temperature estimation: 2. Global comparison with infrared satellite temperature. Issue 6 (14th March 2017) - Ermida, S. L.; Jiménez, C.; Prigent, C.; Trigo, I. F.; DaCamara, C. C.
Abstract: A comparison of land surface temperature ( T s ) derived from the Advanced Microwave Scanning Radiometer–Earth Observing System (AMSR‐E) with infrared T s is presented. The infrared T s include clear‐sky estimates from the Moderate Resolution Imaging Spectroradiometer (MODIS), the Spinning Enhanced Visible and Infrared Imager, the Geostationary Operational Environmental Satellite (GOES) Imager, and the Japanese Meteorological Imager. The higher discrepancies between AMSR‐E and MODIS are observed over deserts and snow‐covered areas. The former seems to be associated with T s underestimation by MODIS, whereas the latter is mostly related to uncertainties in microwave emissivity over snow/ice. T s differences between AMSR‐E and MODIS are significantly reduced after masking out snow and deserts, with a bias change from 2.6/4.6 K to 3.0/1.4 K for daytime/nighttime and a standard deviation (STD) decrease from 7.3/7.9 K to 5.1/3.9 K. When comparing with all infrared sensors, the STD of the differences between microwave and infrared T s is generally higher than between IR retrievals. However, the biases between microwave and infrared T s are, in some cases, of the same order as the ones observed between infrared products. This is the case for GOES, with daytime biases with respect to AMSR‐E and MODIS of 0.45 K and 0.60 K, respectively. While the infrared T s are clear‐sky estimates, AMSR‐E also provides T s under cloudy conditions. For frequently cloudy regions, this results in a large increase of available T s estimates (>250%), making the microwave T s a very powerful complement of the infrared estimates. Key Points: Global comparison of land surface temperature ( Ts ) from multiple sensors (AMSR‐E, MODIS, SEVIRI, GOES, and MTSAT) The use of microwave Ts leads to an increase of more than 250% on the number of available observations Discrepancies between infrared and microwave Ts can be of the same order as the ones between infrared Ts products